Preparation and characterization of polydimethylsiloxane-based composite films - Kilic, Enver Can; Salt, Yavuz (WALTER DE GRUYTER GMBH, 2021)
In this study, we aimed to find the characteristic properties of the neat and the composite polydimethylsiloxane (PDMS) films. The composite films were prepared by adding 5 A and NaY zeolites and nano-TiO2 to PDMS polymer matrix. In the preparation of the composite polymer films, the inorganic additives were added by 10 wt.-%. The structural and thermal characteristics of the prepared homogenous PDMS film and composite PDMS films were determined by Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). The glass transition temperature of the films was found by differential scanning calorimetry (DSC). Finally, the mechanical properties of the films were obtained through tensile tests. The effects of 5 A and NaY zeolites and TiO2 on the neat PDMS films were investigated.
Keywords: Polydimethylsiloxane; zeolite 5 A; zeolite NaY; titaniumdioxide; composite film; ZEOLITE FILMS; DIRECT DECOMPOSITION; MEMBRANES; SEPARATION; PERVAPORATION; FABRICATION; Materials Science